Aged Mice Demonstrate Greater Muscle Degeneration of Chronically Injured Rotator Cuff. Issue 2 (15th October 2019) - Sharma, Abhinav K.; Levian, Brandon; Shah, Paras; Mosich, Gina M.; Husman, Regina; Ariniello, Allison; Gatto, Jonathan D.; Hu, Vivian J.; McClintick, Daniel J.; Jensen, Andrew R.; McAllister, David R.; Péault, Bruno; et al.
ABSTRACT: Massive tears of the rotator cuff (RC) are often associated with progressive and irreversible muscle degeneration due to fibrosis, fatty infiltration, and muscle atrophy. RC tears are common in individuals older than 60 years and the repair of these tears is amongst the most prevalent of orthopedic procedures. However, most current models of this injury are established in young animals, which may not accurately recapitulate the clinical condition. In this study, we used a murine model of massive RC tears to evaluate age‐related muscle degeneration following chronic injury. The expression of the fibro‐adipogenic genes encoding collagen type III and leptin was higher in aged RC compared with matched injured young tissue at 2 weeks post‐injury, and development of fibrosis was accelerated in aged mice within 5 days post‐injury. Furthermore, the synthesis of collagens type I and III and fat tissue accumulation were significantly higher in injured RCs of aged mice. Similar frequency of fibro‐adipogenic PDGFRβ + PDGFRα + progenitor cells was measured in non‐injured RC of aged and young mice, but PDGFRβ + PDGFRα + cells contributed to significantly larger fibrotic lesions in aged RCs within 2 weeks post‐injury, implying a more robust fibrotic environment in the aged injured muscle. Altogether, these findings demonstrate age‐dependent differences in RC response to chronic injury with a more profound fibro‐adipogenic change in aged muscles. Clinically, cell therapies for muscular pathologies should not only consider the cell type being transplanted but also the recipient milieu into which these cells are seeded. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:320‐328, 2020